2013
DOI: 10.1113/jphysiol.2013.261420
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous zinc depresses GABAergic transmission via T‐type Ca2+ channels and broadens the time window for integration of glutamatergic inputs in dentate granule cells

Abstract: Zinc actions on synaptic transmission span the modulation of neurotransmitter receptors, transporters, activation of intracellular cascades and alterations in gene expression. Whether and how zinc affects inhibitory synaptic signalling in the dentate gyrus remains largely unexplored. We found that mono- and di-synaptic GABAergic inputs onto dentate granule cells were reversibly depressed by exogenous zinc application and enhanced by zinc chelation. Blocking T-type Ca2+ channels prevented the effect of zinc che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Although previous studies reveal that vesicular zinc is released during neurotransmission (7-9, 12, 13, 58, 59), there remains a controversy about whether released synaptic zinc is free to diffuse, or whether it contributes to the generation of a tonic level of zinc in the extracellular space (3,5,10,60). Our results in the DCN show that, in response to brief trains of synaptic stimuli, phasic release of synaptic/vesicular zinc modulates extrasynaptic NMDARs.…”
Section: Discussion Synaptic and Tonic Zinc Are Endogenous Modulatorsmentioning
confidence: 53%
“…Although previous studies reveal that vesicular zinc is released during neurotransmission (7-9, 12, 13, 58, 59), there remains a controversy about whether released synaptic zinc is free to diffuse, or whether it contributes to the generation of a tonic level of zinc in the extracellular space (3,5,10,60). Our results in the DCN show that, in response to brief trains of synaptic stimuli, phasic release of synaptic/vesicular zinc modulates extrasynaptic NMDARs.…”
Section: Discussion Synaptic and Tonic Zinc Are Endogenous Modulatorsmentioning
confidence: 53%
“…Studies support that vitamin E and selegiline could slow or stop Mild Cognitive Impairment (MCI) to moderate/severe NCD conversion (8,9). Zinc is an element that has widespread function within neurons, including binding to metal-binding proteins, and the modulation of presynaptic, synaptic, and postsynaptic neurotransmitter receptors, such as Nmethyl-d-aspartate and Gamma-aminobutyric acid (10)(11)(12). Therefore, the homeostasis of zinc has a critical role in the maintenance of normal cellular processing.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, it was recently reported that chelating zinc with TPEN could facilitate modulation of GABAergic inhibitory post‐synaptic currents in hippocampal granule cells, an effect that was occluded when blocking T‐type channels (Grauert et al . ). Increased Cav3.2 channel activity due to the removal of a chelatable zinc fraction would enhance cellular excitability in fast‐spiking interneurons without affecting the properties of granule cells, supporting that zinc modulation of GABAergic transmission to granule cells would involve H191‐dependent regulation of Cav3.2 channels.…”
Section: Discussionmentioning
confidence: 97%
“…This redox modulation of Cav3.2 channels could also be involved in the GABA B receptor inhibition of T-type channels in DRG neurons (Huang et al 2015). Of interest, it was recently reported that chelating zinc with TPEN could facilitate modulation of GABAergic inhibitory post-synaptic currents in hippocampal granule cells, an effect that was occluded when blocking T-type channels (Grauert et al 2014). Increased Cav3.2 channel activity due to the removal of a chelatable zinc fraction would enhance cellular excitability in fast-spiking interneurons without affecting the properties of granule cells, supporting that zinc modulation of GABAergic transmission to granule *** *** *** (11) (10) (8) (6) (6) (6) (5) (8) (13) (7) (7) (…”
Section: Metal/redox Sensitivity Of T-type Currents In Drg Neurons mentioning
confidence: 99%